Novel roles of κ-opioid receptor in myocardial ischemia-reperfusion injury - Zhang, Wen; Zhang, Qi; Liu, Yali; Pei, Jianming; Feng, Na (PeerJ, 2024)
Acute heart attack is the primary cause of cardiovascular-related death worldwide. A common treatment is reperfusion of ischemic tissue, which can cause irreversible damage to the myocardium. The number of mitochondria in cardiomyocytes is large, which generate adenosine triphosphate (ATP) to sustain proper cardiac contractile function, and mitochondrial dysfunction plays a crucial role in cell death during myocardial ischemia-reperfusion, leading to an increasing number of studies investigating the impact of mitochondria on ischemia-reperfusion injury. The disarray of mitochondrial dynamics, excessive Ca2+ accumulation, activation of mitochondrial permeable transition pores, swelling of mitochondria, ultimately the death of cardiomyocyte are the consequences of ischemia-reperfusion injury. κ-opioid receptors can alleviate mitochondrial dysfunction, regulate mitochondrial dynamics, mitigate myocardial ischemia-reperfusion injury, exert protective effects on myocardium. The mechanism of κ-OR activation during myocardial ischemia-reperfusion to regulate mitochondrial dynamics and reduce myocardial ischemia-reperfusion injury will be discussed, so as to provide theoretical basis for the protection of ischemic myocardium.
Keywords: Myocardial ischemia-reperfusion injury; κ-opioid receptor; Mitochondria; Cardiac protection